ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI PERTUMBUHAN LABA PERUSAHAAN - Novita Dwi Utami; Ruliaty Ruliaty (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
This research was conducted to test the influence of Variable Working Capital to Total Asset (WCTA), Current Liabilities To Inventory (CLI), Operating Income to Total Assets (OITL), Total Asset Turnover (TAT), Net Profit Margin (NPM) and Gross Profit Margin (GPM) on profit growth. The data was obtained by purposive sampling method with the criteria of Multi-Industry Manufacturing Companies in the automotive sector and components listed on the Indonesia Stock Exchange (IDX) in 2012-2016.The results of the analysis showed that the data used in this study have fulfilled classical assumptions, which include: no symptoms of multicolinearity, no autocorrelation, no symptoms of heterosceticity, and normal distributed data. From the results of regression analysis shows that variable Working Capital to Total Asset (WCTA), Current Liabilities To Inventory (CLI), Net Profit Margin (NPM) and Gross Profit Margin (GPM) have a significant positive effect on profit growth. While the variables Operating Income to Total Assets (OITL) and Total Asset Turnover (TAT), have no significant effect on profit growth. The six variables used in this study (WCTA, CLI, OITL, TAT, NPM and GPM) jointly influenced profit growth. Keywords: Working Capital to Total Asset (WCTA), Current Liabilities To Inventory (CLI), Operating Income to Total Assets (OITL), Total Asset Turnover (TAT), Net Profit Margin (NPM), Gross Profit Margin (GPM) and profit growth.